Pengaruh Pengeluaran Pemerintah Bidang Ekonomi dan Pelayanan Umum terhadap Pertumbuhan Ekonomi di Provinsi Jambi - Angraini, Deva; Fathiyah, Fathiyah; Masnun, Masnun (Universitas Batanghari Jambi, 2023)
The purpose of this study is aimed at knowing (1) The effect of government spending on the economy and public services on economic growth in Jambi Province. (2) Effect of government spending on public services on economic growth in Jambi Province. (3) The effect of government spending on the economy and public services simultaneously on economic growth in Jambi Province. The data used in this study are secondary data obtained from the official website of the Central Statistics Agency and the Directorate General of Fiscal Balance. The population used in this study were all regencies and cities in Jambi Province in 2014-2018, amounting to 55. This study used the Fixed Effect Model panel data regression analysis tool. The results showed that: (1) government spending in the economy had a significant effect on economic growth, indicated by the value of 1.766245> t table 1.29837. (2) government spending on public services does not have a significant effect on economic growth, as indicated by the value of tcount 0.952926 <ttabel 1.29837 (3) government spending on the economy and public services simultaneously influencing economic growth is indicated by the value of Fcount 12.86652> Ftable 3.18. and the coefficient of determination (Adj R2) 0.725.